DO TEXTO À TELA: PESQUISA-AÇÃO SOBRE LEITURA LITERÁRIA DE CRÔNICA TENDO O CURTA-METRAGEM COMO TRADUÇÃO - Ana, Claudia Rodrigues de Sant (2022)
The present work aims to investigate how the first grade high school students from a state public school printed their counterwords while they were producing a short film, after working with the chronic literary genre, which is part of the research group "Literature and Education” discussions. We have selected as an object of the research the text "Mourning of the Silva´s Family" (1935), by Rubem Braga. The research was based on the reflections about the literature teaching as a possibility of the individual humanization (CANDIDO, 2004); in the defense of the school as a place for the elaborated knowledge transmission, according to the historical-critical pedagogy (SAVIANI, 2011), and in the conception that the classroom is the propitious place for the language in a dialogical perspective development (BAKHTIN, 2003; 2004). The goal was promotting the work with the literary text, which allowed the participation of the readers in the text events and the interaction between the subjects. This investigation was carried out in two moments: the first was based on the bibliographic-documentary study; and the second was based on an action research, which consisted of an interventional activity application in which the results were analyzed through a questionnaire and by the counterwords materialized in the audiovisual. From the analyses, we found that: a) dialogue and mediation should be the path taken before, during and after the activity of reading the literary text, because these are indispensable factors for the understanding of the object; b) the dialogical relationship promoted throughout the proposal was essential to identify that students have their own statements and are able to produce them; c) the reflections raised by the full reading of the work allowed us to verify that many personal experiences lived by the students contributed to associating the plot with their daily situations; d) the reading of the chronicle provided students with a critical view of reality and the participants had the possibility to create utterances and print their counterwords in them; e) the short film proved to be an educational instrument able to help the opinions formation, serving as a support for the translation of the literary text.